SOSIALISASI PERPAJAKAN MEMODERASI PENGARUH KESADARAN WAJIB PAJAK DAN KUALITAS PELAYANAN PADA KEPATUHAN WAJIB PAJAK BADAN - Megawangi, Cokorda Agung Meggy; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
Normal 0 false false false EN-US X-NONE X-NONE The purpose of this research is to know how to influence taxpayer awareness and quality service on taxpayer compliance with the socialization of taxation as a moderating. Research conducted at the Tax Office Primary Gianyar. The sampling is done through convenience sampling method, then the sample size was calculated using the formula Slovin using 100 samples. Methods of data analysis done by Moderated Regression Analysis (MRA). The results showed that awareness of the taxpayer and a significant positive effect on tax compliance body. Service quality and significant positive effect on tax compliance body. The results also indicate that the socialization of taxation able to moderate the influence of awareness of taxpayers on tax compliance body. Socialization taxation also able to moderate the influence of service quality on taxpayer compliance.
Keywords: taxpayer awareness, quality of services, tax compliance, and socialization taxation.